Cara Mengembangkan Mengajar Aktif untuk Siswa Sekolah Dasar - Feny Carollina (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2017)
Professional teachers are teachers who are capable of designing learning and achieving the objectives of the learning. Among them are making teaching plans, establishing models, strategies and learning methods. In preparing the teaching plan selection of models and appropriate strategies will foster student interest in learning. The existence of media used as a messenger from the teacher to students. The determination of models, methods, strategies, and media must be balanced with the emphasis of the students' own knowledge, skills, and attitudes. All of it into a single unit that is designed well for the purpose can be achieved. Professional teachers must create a fun situation in the classroom by mastering various theories as well as the types of learning.